Oral Health in Rheumatoid Arthritis: Listening to Patients. (April 2022) - Protudjer, J.L.P.; Billedeau, C.; Hurst, K.; Schroth, R.; Stavropoulou, C.; Kelekis-Cholakis, A.; Hitchon, C.A.
Introduction: Rates of periodontal disease and tooth loss are increased in individuals with rheumatoid arthritis (RA). Understanding factors that contribute to the increased burden of periodontal disease in RA is critical to improving oral health and arthritis outcomes. Objectives: To determine the perceptions held by people with RA relating to their oral health, to identify patient-centered priorities for oral health research, and to inform optimal strategies for delivering oral health knowledge. Methods: Semistructured interviews were conducted with patients with RA. Recorded interview transcripts were iteratively reviewed to reveal surface and latent meaning and to code for themes. Constructs were considered saturated when no new themes were identified in subsequent interviews. We report themes with representative quotes. Results: Interviews were conducted with 11 individuals with RA (10 women [91%]; mean age, 68 y), all of whom were taking RA medication. Interviews averaged 19 min (range, 8 to 31 min) and were mostly conducted face-to-face. Three overall themes were identified: 1) knowledge about arthritis and oral health links; 2) oral health care in RA is complicated, both in personal hygiene practices and in professional oral care; and 3) poor oral health is a source of shame. Participants preferred to receive oral health education from their rheumatologists or dentists. Conclusions: People with RA have unique oral health perceptions and experience significant challenges with oral health care due to their arthritis. Adapting oral hygiene recommendations and professional oral care delivery to the needs of those with arthritis are patient priorities and are required to improve satisfaction regarding their oral health. Knowledge Translation Statement: Patients living with long-standing rheumatoid arthritis described poor oral health–related quality of life and multiple challenges with maintaining optimal oral health. Study findings indicate a need for educational materials addressing oral health maintenance for patients with rheumatic diseases and their providers.